Responsible tourism system dynamic planning model for rural area - Khoo, Wen Keat (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Rural Tourism in Malaysia has potential to grow and contribute significantly to the development of Malaysia. However, sustainability is the barrier in the tourism development path. Responsible Tourism(RT) is a new movement which claims to improve sustainability in Malaysia tourism industry. A dynamic simulation model has been developed to assist decision makers in RT development. Lundu is chosen as a destination in structuring the causal loop diagram to understand the dynamic relationship between environment, tourism and local population. A simulation model is formed by implementing mathematical equations into the causal loop diagram. In this model, several scenarios were used to simulate the data obtained and results generated were being analyzed. Validation of the model in usability is done by a few research officers in tourism field. Key indicators have to be refined in the model to improve the effectiveness and consistency with reality. This study shows that system dynamic modelling is an effective and powerful tool to help in simplify the complex tourism system by presenting a large interrelation image associated with the industry. It helps in decision making to achieve disirable outcomes.